2020
DOI: 10.1111/all.14410
|View full text |Cite
|
Sign up to set email alerts
|

Effect of structural stability on endolysosomal degradation and T‐cell reactivity of major shrimp allergen tropomyosin

Abstract: Background Tropomyosins are highly conserved proteins, an attribute that forms the molecular basis for their IgE antibody cross‐reactivity. Despite sequence similarities, their allergenicity varies greatly between ingested and inhaled invertebrate sources. In this study, we investigated the relationship between the structural stability of different tropomyosins, their endolysosomal degradation patterns, and T‐cell reactivity. Methods We investigated the differences between four tropomyosins—the major shrimp al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…This is in line with the enhanced susceptibility to proteases of L89G observed in the degradome assay. We have previously found that immunodominant peptides from Bet v 1.0101 or tropomyosin (55,62) are quickly degraded in the degradome assay, but nevertheless are effectively presented by BMDCs in vitro, supporting the concept of "bind first, cut later." Kim et al have shown that immunodominant epitopes are protected from further degradation by binding to MHC II, whereas epitopes sensitive to DM-mediated dissociation are destroyed by cathepsins (57,63).…”
Section: Discussionmentioning
confidence: 63%
“…This is in line with the enhanced susceptibility to proteases of L89G observed in the degradome assay. We have previously found that immunodominant peptides from Bet v 1.0101 or tropomyosin (55,62) are quickly degraded in the degradome assay, but nevertheless are effectively presented by BMDCs in vitro, supporting the concept of "bind first, cut later." Kim et al have shown that immunodominant epitopes are protected from further degradation by binding to MHC II, whereas epitopes sensitive to DM-mediated dissociation are destroyed by cathepsins (57,63).…”
Section: Discussionmentioning
confidence: 63%
“…The blocked-nitrocellulose membrane was incubated overnight with a pooled serum from five shellfish-allergic patients ( Table 2 ) diluted 1:20 in PBST with added casein. After the washing step, secondary anti-human IgE (1:10,000 dilution, DAKO Corporation, Lincoln, NE, USA) was added and incubated for 1 h. The membrane was subsequently incubated for 35 min with donkey anti-rabbit IgG antibody conjugated infrared IRDye 800CW (1:10,000 dilution, LI-COR, Lincoln, NE, USA), and IgE antibody binding was visualised using the Odyssey ® CLx Imaging System (LI-COR Biosciences, Mulgrave, VIC, Australia) [ 17 ]. IgE reactive spots were annotated to the protein profile on SDS-PAGE, and corresponding bands cut out, tryptic digested and analysed using mass spectrometry.…”
Section: Methodsmentioning
confidence: 99%
“…Even with this expanded understanding it is important to remember that exceptions will always exist. For instance, a survey of tropomyosin allergens from both food (Pen m 1, Shrimp; Ani s 3, fish parasite) and environmental (Der p 10, dust mite; Bla g 7, cockroach) sources revealed significant variation in both thermodynamic stability and endosomal degradation kinetics ( 110 ). However, neither measure of stability was found to correlate with allergenicity.…”
Section: Antigen Presentation Kinetics and Stability Influence Allerg...mentioning
confidence: 99%